2019
DOI: 10.23937/2469-5734/1510080
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries in Geriatric Dentistry: An Update for Clinicians

Abstract: and dependence are accompanied by degradation in oral status with an increased development of gingival and carious pathologies [10,11]. Location and distributionIn the elderly, caries mostly affects teeth roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Factors associated with ageing also increase the risk of dental caries in older adults due to an ecological imbalance in oral biofilm, leading to the demineralisation of teeth [ 12 ]. This is shown by the Centre for Disease Control and Prevention (CDC), which reported that 96% of adults aged 65 years or older have had at least one cavity, whilst one in five suffer from untreated tooth decay [ 6 ].…”
Section: How Does Inadequate Protein Intake Affect Saliva and Oral He...mentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with ageing also increase the risk of dental caries in older adults due to an ecological imbalance in oral biofilm, leading to the demineralisation of teeth [ 12 ]. This is shown by the Centre for Disease Control and Prevention (CDC), which reported that 96% of adults aged 65 years or older have had at least one cavity, whilst one in five suffer from untreated tooth decay [ 6 ].…”
Section: How Does Inadequate Protein Intake Affect Saliva and Oral He...mentioning
confidence: 99%
“…Periodontitis is associated with chronic diseases, particularly hyperglycemic states associated with poorly controlled diabetes mellitus [ 9 ], cardiovascular disease [ 10 ] and chronic kidney disease [ 11 ]. Factors associated with ageing also increase the risk of dental caries (tooth decay) in older adults due to an ecological imbalance in oral biofilm, leading to the demineralisation of teeth [ 12 ]. A recent systematic review reported that 50% or more of older adults had untreated dental caries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of prioritization of oral health, both among care-dependent older adults and among the nursing staff [ 62 ]. This could be attributed to insufficient knowledge of the connection between poor oral health and systemic diseases [ 2 ]. It is an important task for the dental profession to provide this knowledge before or in the early stages of care dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Among care-dependent older adults living in nursing homes, the number of untreated root caries lesions (RCLs) is high [ 1 , 2 ]. A systematic review by Zhang et al [ 3 ] discovered several risk predictors for developing RCLs.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the world, dental caries is a major oral health problem in children, adults 1,2 , pregnant women 3,4 , and elderly. 5,6 The incidence of dental caries in developing countries, especially in Indonesia, is still quite high. As many as 45.…”
Section: Introductionmentioning
confidence: 99%